Physical Environmental Factors and Its Association with the Existence of Mycobacterium Tuberculosis: A Study in The Working Region of Perak Timur Public Health Center - Diah Dwi Lestari Muslimah (JURNAL KESEHATAN LINGKUNGAN, 2019)
In 2017, Surabaya District Health Office reported an increasing number of new cases of pulmonary tuberculosis in the working region of of East Perak Surabaya Public Health Center (Puskesmas) and was reported as the highest rates of tuberculosis cases in Surabaya. Pulmonary tuberculosis can be transmitted through ambient air contamination initiated by the presence of Mycobacterium tuberculosis. This study aims to determine the association of physical environmental factors (temperature, humidity, lighting, ventilations' size, floor materials, walls, ceilings, and density) in the presence of Mycobacterium tuberculosis in the air. This research is an observational analytic study with case control study design. The study sample consisted of 21 households/realtives of patients diagnosed with Pulmonary TB positive. The data was obtained from completed questionnaires by respondents, direct observation and laboratory examination of the presence of Mycobacterium tuberculosis in the air. Data analysis was conducted by Chi-square test supported by Fisher's Exact Test test. The results showed that the significant association between physical environment variables of temperature variables (p-value= 0,000), humidity (p-value= 0,000), lighting (p = 0,000), with the existence of mycobacterium tuberculosis inside of the room. While insignificant association was detected for the variables of ventilation (p = 0.397), floor materials (p = 0.229), the walls materials (p = 0.338), the ceiling condition (p = 0.331), and the dwellers density (p = 0.611), with the presence of Mycobacterium tuberculosis in the air of the common room this current study concludes that there is a significant association between temperature, humidity, and illumination with the presence of Mycobacterium tuberculosis in ambient of common room. Transmission of tuberculosis can be eliminated by using face masks, Despite the previous satisfied level of knowledge, the family behavior and practices when in contact with patients were insufficient to prevent pulmonary TB transmission.